2019
DOI: 10.1002/osp4.328
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of liraglutide in Indian adolescents with obesity

Abstract: Summary Aim The aim of this study was to evaluate the efficacy and safety of liraglutide in adolescents with obesity. Materials and methods Patients ( n = 41) received injection liraglutide for at least 12 weeks and their pre‐baseline and post‐baseline characteristics were recorded and analysed. The key parameters analysed were weight, height, body mass index (BMI), fasting insulin and sugar, 1 h insulin and glucose, 2 h insulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This study aimed to identify the efficacy of liraglutide on weight, HbA1c, and blood pressure in Saudi patients with T2D who attended KFUH and received liraglutide as add-on therapy to other antihyperglycemic agents. While similar studies have been conducted on other ethnic populations [ 14 , 15 ], this study is the first such study conducted in a Saudi population.…”
Section: Discussionmentioning
confidence: 85%
“…This study aimed to identify the efficacy of liraglutide on weight, HbA1c, and blood pressure in Saudi patients with T2D who attended KFUH and received liraglutide as add-on therapy to other antihyperglycemic agents. While similar studies have been conducted on other ethnic populations [ 14 , 15 ], this study is the first such study conducted in a Saudi population.…”
Section: Discussionmentioning
confidence: 85%
“…The study showed that 51% of patients lost 5%–10% of their body weight and 23% lost over 10% 74 . The results also demonstrated a significant improvement in systolic blood pressure, insulin, glucose, HbA1c and lipid profile levels and liver function tests 74 …”
Section: Definitionmentioning
confidence: 91%
“…Evidence from trials of T2DM suggests that weight loss is achieved with higher doses of liraglutide, as shown by Kochar et al 74 The safety of such doses was established by Danne et al 75 in a double‐blind RCT which had a sample size of 21 adolescents. Liraglutide was given once daily for 5 weeks, with a maximal dose of 3 mg.…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations